2007
DOI: 10.1038/ng2111
|View full text |Cite
|
Sign up to set email alerts
|

Unusual selection on the KIR3DL1/S1 natural killer cell receptor in Africans

Abstract: Interactions of killer cell immunoglobulin-like receptors (KIRs) with major histocompatibility complex (MHC) class I ligands diversify natural killer cell responses to infection. By analyzing sequence variation in diverse human populations, we show that the KIR3DL1/S1 locus encodes two lineages of polymorphic inhibitory KIR3DL1 allotypes that recognize Bw4 epitopes of protein">HLA-A and HLA-B and one lineage of conserved activating KIR3DS1 allotypes, also implicated in Bw4 recognition. Balancing selection has … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

30
306
2
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 208 publications
(339 citation statements)
references
References 50 publications
30
306
2
1
Order By: Relevance
“…This suggests that more KIR2DL5 polymorphisms are likely to be discovered in Africans. Consistent with this finding, extensive polymorphism was also observed at the KIR3DL1/S1 locus in African populations 22 indicating …”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…This suggests that more KIR2DL5 polymorphisms are likely to be discovered in Africans. Consistent with this finding, extensive polymorphism was also observed at the KIR3DL1/S1 locus in African populations 22 indicating …”
Section: Discussionsupporting
confidence: 74%
“…This is very different from the scenario seen in KIR3DL1, which has been shown to be highly polymorphic with enriched amino-acid substitutions in the ligand-binding loops. 22,25 Confined variations in the ligand-binding sites of KIR3DL1 have been considered to be driven by coevolving polymorphic HLA-B and HLA-A ligands. 22,26 The conserved nature of KIR2DL5 suggests the possibility that it recognizes an invariant determinant.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A good example is KIR3DL1/S1 , which has over 100 alleles characterized (Fig. 4)60 and has three divergent allele lineages that have been maintained by balancing selection for millions of years 61. A synergy of population genetics, phylogenetic analysis and comparison of nucleotide substitution rates among codons showed that this diversity is focused towards the parts of the KIR molecule that bind the HLA class I and peptide 61.…”
Section: Kir Geneticsmentioning
confidence: 99%
“…4)60 and has three divergent allele lineages that have been maintained by balancing selection for millions of years 61. A synergy of population genetics, phylogenetic analysis and comparison of nucleotide substitution rates among codons showed that this diversity is focused towards the parts of the KIR molecule that bind the HLA class I and peptide 61. The prediction that these major lineages of KIR3DL1/S1 have distinct ligand HLA/peptide‐binding properties has been borne out with crystallographic and functional studies 35, 39, 41, 42, 62, 63, 64, 65.…”
Section: Kir Geneticsmentioning
confidence: 99%